Establishment of the national science-policy dialogue platform on climate change, agriculture and food security in the framework of the ProPAD project in CHAD: Technical workshop report - Ogou, Anani; Ouedraogo, Adama; Zakaria, Mahamat Nour; Youssouf, Mahamat Abdelkerim; Kagabo, Desire M.; Ouedraogo, Mathieu; Laderach, Peter (2023)
The Science-Policy Dialogue Platform Establishment Workshop held from 14 to 15 December 2023 at the ‘’Amitié Hotel’’ in N'Djamena, Chad aimed to create a framework and enabling environment for evidence-based policymaking to mitigate the risks of climate change and variability in Chad. The workshop was attended by 25 out of 35 expected institutions. The participants (20) were of high quality, and this made it possible to produce exchanges aimed at useful proposals. In terms of results, the workshop identified the country's challenges in terms of including scientific evidences in agricultural policies on climate change related issues. Thus, the implications of these challenges and solutions to achieve this synergy were proposed by the participants. A deadline for formalization and a provisional team have been proposed. The workshop also recommended that CORAF and CIAT continue to support actors towards legal formalization, institutional anchoring and operationalization of the National CCAFS Science-Policy Dialogue Platform in Chad.